Relationship between on-the-job training and work performance among academic staff in Universiti Teknologi MARA, Machang Campus, Kelantan / Muhammad Azim Shah Rusli - Rusli, Muhammad Azim Shah (2014)
Research has found that the on the - job training were partially successful in realizing the training goals and also in the immediate effect explanation training was satisfactory (Klink & Streumer, 2002). This study reports the relationship between on the job training and work performance among academic staff at Universiti Teknologi MARA, Machang Campus, Kelantan. Many organizations and learning institutions in Malaysia have implemented on the job training because of its effectiveness as a training approach. However, studies have shown that academic staffs are apprehensive about the types of training that relate to their work performance in their career. The theoretical framework for this study is based on conceptual framework. Two dimensions representing independent variables that contribute to the work performance which is on the job training. Data are gathered through surveys among the academic staffs in one of the Universiti Teknologi MARA branches in Kelantan which implemented on the job training. Among the dimension which influenced the level of effectiveness of on the job training are coaching and internship. Findings from this study provided insights on the attitude, academic staffs towards the level of effectiveness of on the job training. Its practical contribution includes other types of on the job training and psychological trainers which can be incorporated into the on the job training program to address the improvement of low effectiveness on the -job training dimension which are coaching and internship.